Focused Written Corrective Feedback: EFL Students’ Engagement in Online Asynchronous Platform - Nurfaidah, Sitti (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This study is intended to investigate the students’ engagement on teacher’s focused written corrective feedback (FWCF) on their writing in online asynchronous platform. Data gathered from students’ written drafts and reflective journal were analyzed using Ferris’ (2012) FWCF framework as well as sociocultural and activity framework in the online instructional setting. The findings of the study indicate that the students’ cognitive, behavioral, and affective engagement in online asynchronous platform with FWCF portray their learning beliefs as they are exposed to written feedback. Students engagement with online FWCF reveal that such online platform feedback helps students check their progress without time and place boundary. Such feedback also facilitates them to do self-revision because the feedback raises their awareness of their mistakes leading them into more autonomous learners. Moreover, the online platform is considered to be effective due to its mobility. Students’ only complaint is when they are encountered with limited data usage and network around campus.Keywords:Asynchronous; EFL writing; online platform; focused written corrective feedback